Consensus building as a way of enhancing basic education in Nigeria - Abdullahi, Danjuma; Abdullah, Siti Alida John; Abdulsomad, Kammaruddin (2014)
Modern government operate by networking with other institutions such as nongovernmental organizations, family, private organization, unions etc for the achievement of aims and objectives of the government policy, such networking depend on the commitment from the stakeholders or parties involved. But in Nigeria the delivery of basic education lacks collaboration which create problems in basic education such as poor infrastructures, dilapidated buildings, influx of teachers from the teaching profession in search for greener pasture and increase in drop out.The paper relied on interviews, documents, newspapers and periodic reports of the organization in focus. The findings revealed lack of proper coordination of the programme as a result there are many out of school children in the state, the paper recommends increase in collaboration between the stakeholder in order to achieved millennium development goals (primary education) as well as vision 2020.